Governor's Digital Education Campaign (Greeting Style) in the Prevention of the Covid-19 Pandemic Transmission in Central Java, Indonesia - Agus Naryono; Rintulebda Anggung Kaloka; Mj Rizqon Hasani (Journal of Social Research, 2023)
Central Java is a province that ranks in the top three with the highest number of cases exposed to Covid-19 in Indonesia. During the pandemic situation, the Central Java Provincial Government intensively carried out a digital campaign to fight the spread and transmission of the virus. The digital campaign contains a number of health protocol educational videos conducted by the governor and published through official social media accounts, such as Youtube and Instagram. This study aims to describe the public's attitude towards health protocol education carried out by Governor Ganjar Pranowo through this digital campaign. Rhetoric theory is used as a basis for explaining the success aspects of digital campaigns. This type of research is descriptive quantitative research. Primary data were obtained through online surveys. As many 19 questions were asked to respondents. A total of 121 respondents participated by voluntary sampling in the online survey. Respondents' answers were then processed using SPSS. The research findings show that the respondents show a positive attitude towards the Covid-19 digital campaign conducted by the Central Java Provincial Government. Respondents considered that the digital campaign was a creative step taken by the Central Java Provincial Government to educate the public in the midst of a pandemic situation.